Chemical Synthesis and Gas Chromatographic Behaviour of γ‐Stearidonic (18:4n‐6) Acid. (22nd January 2015) - Vyssotski, Mikhail; Lagutin, Kirill; MacKenzie, Andrew; Itabashi, Yutaka
Abstract: γ‐Stearidonic acid, 18:4n‐6, a potential product of β‐oxidation of arachidonic acid (20:4n‐6), was only recently positively identified in a living organism—a thermophilic cyanobacterium Tolypothrix sp., albeit at low levels, whilst some indirect evidence suggests its wider presence, e.g. in a unicellular marine alga. We have prepared 18:4n‐6 using an iodolactonisation chain‐shortening approach from 22:5n‐6 and obtained its 1 H‐, 13 C‐, COSY‐ and HSQC NMR spectra, with 18:5n‐3 spectra also recorded for a comparison. The GC and GC‐MS behaviour of its methyl ester was also studied. Like another Δ3 polyunsaturated acid, octadecapentaenoic (18:5n‐3), 18:4n‐6 rapidly yields 2‐ trans isomer upon formation of dimethyloxazoline derivative. On a polar ionic liquid phase (SLB‐IL100, 200 °C) the methyl ester could be mistaken for 18:3n‐3, while on methylsilicone phase (BP1, 210 °C) it eluted ahead of 18:3n‐6 and 18:4n‐3, suggesting that when present it may be easily misidentified during GC analysis of fatty acids.